Futebol e religião: a devoção dos adeptos portugueses - Gouveia, C.; Tavares, A. T.; David, A. (Observatorio del Deporte, 2019)
Football and religion are both terms that carry among them an enormous reality, embrace a diversity of rules, rituals and conventions, even though they are populated by multiple contradictions. In this sense, the article explores both football and religion social dimensions, according to reflections already made by different authors. Aiming to understand in which way the collective belief, ritualism or totem may be viewed as factors that operate sideways to the experiences felt and lived by the fans of the sport in the Portuguese championship. The methodology adopted is based on the questionnaire survey, whose construction was based on the theoretical problematization, in order to measure the various attributes associated with the dimensions of belief, ritual and use of totemic objects. It was applied to a non-probabilistic convenience sample composed by 488 individuals. Through the analysis and interpretation of the main data, we verified the existence of attributes associated to the three dimensions under analysis. It is argued based on the conclusions obtained that football can be understood as a practical cultural with attributes comparable to religion in which elements like collective belief, ritualism or totem can be viewed as side factors to the actions or reactions of the fans.